Infection in a Young Immunocompetent Male Caused by Streptobacillus felis, a Putative Zoonotic Microorganism Transmitted by Cats. (13th July 2020) - Matt, Ulrich; Schmiedel, Judith; Fawzy, Ahmad; Trauth, Janina; Schmidt, Katja; Vogel, Klaus; Herold, Susanne; Karrasch, Thomas; Imirzalioglu, Can; Eisenberg, Tobias
Abstract: Rat bite fever (RBF) is predominantly caused by Streptobacillus moniliformis . We report a human infection with Streptobacillus felis . Clinical presentation was consistent with RBF, but serologic testing was negative for S moniliformis . Eventually, S felis –specific sequences were detected in skin lesions of the patient and in the oropharynx of local cats.